Peningkatan Pemahaman Pembuatan Pala Instan Metode Foam Mat Drying Bagi Siswa SMK Negeri H. Moenadi Ungaran Kabupaten Semarang - kunarto, bambang (Universitas Semarang, 2025)
One of the processed nutmeg fruit products is instant powdered drink, which can be made using the foam mat drying method. This activity aims to increase the understanding of class XII students at SMK Negeri H. Moenadi Ungaran regarding the process of making instant nutmeg using the foam mat drying method. The activity began with filling out a questionnaire (pre-test) for 52 students followed by counseling. After the counseling is complete, evaluation is carried out by giving another questionnaire (post-test) to measure the increase in understanding of the material that has been presented. The pre-test and post-test data were then analyzed using the T-test to evaluate significant differences in understanding before and after counseling. Based on the activities that have been carried out, it can be concluded that this outreach activity can increase the understanding of class XII students majoring in APHP-SMK Negeri H. Moenadi about making instant nutmeg using the foam mat drying method Foam mat drying, instant Nutmeg, SMK N. H. Moenadi,.